Kangaroo Mother Care with Integrated Sensors for Vital Sign Monitoring in Low Birth Weight Infants - Muliani; Sarliana; Abd. Farid Lewa (Poltekkes Kemenkes Palu, 2026)
Background: Low birth weight (LBW) infants are at high risk of thermoregulatory, cardiovascular, and respiratory disorders, requiring accurate monitoring of vital signs. The limitations of continuous monitoring devices in healthcare facilities have prompted the development of sensor-based Kangaroo Mother Care (KMC) slings. This study aimed to assess the diagnostic accuracy of temperature, pulse rate (HR), and oxygen saturation (SpO₂) sensors on KMC slings compared to standard hospital medical devices. Methods: A cross-sectional comparative study was conducted on 31 LBW babies who underwent KMC treatment in the Perinatology room at Ampana Hospital from June to September 2025. Temperature, pulse, and SpO₂ measurements were simultaneously obtained using wearable sensors on KMC slings and standard devices, including clinical digital thermometers, neonatal multiparameter/ECG monitors, and medical pulse oximeters. The analysis includes sensitivity, specificity, and positive and negative predictive values. Results: The temperature sensor shows a sensitivity of 90.9% and a specificity of 66.7%. The HR sensor has a sensitivity of 77.8% and a specificity of 86.4%. The SpO₂ sensor shows a sensitivity of 88.0% and a specificity of 64.0%. These values demonstrate a fairly good abnormality detection rate, but still show limitations in consistently distinguishing normal physiological conditions from standard clinical devices. Conclusion: The sensor on the KMC sling shows moderate diagnostic performance and does not yet match the accuracy of standard clinical devices. Given the limitations of the design and sample size, these findings need to be interpreted with caution. These devices have the potential to be used as an initial monitoring or screening support tool in the context of KMC, but require further technical development and validation before wider implementation.